Active learning education in Museum - İrem Namli Altintas; Çiğdem Kozaner Yenigül (International Journal of Evaluation and Research in Education (IJERE), 2020)
In this study, it was aimed to determine social studies candidates how to practice about make of use museums as a learning environment. It was tried to discuss a case, for this purpose ıt was used case study. The study group consisted of 19 students (12 females, 7 males) studying social studies at a public university. Participants were given museum training lasting 7 weeks and the process started with the visit of the Antalya Archeology Museum. In this study, Museum Evaluation Forms were used as data collection tools. These forms were used at two-stage. The first stage was the Pre-Museum Evaluation Form and the second stage was the Activity Evaluation Forms. Content analysis technique was used in data analysis, and the forms were examined separately and themes and categories were created. In the categories, the statements of some of the participants were given with direct quotations. As a result of the research, the expectations of the students before the museum training are divided into the categories of Learning about the use of the Museum, Historical awareness and Embodiment in the theme of Cognitive Field. In the affective main theme, it was determined that it was divided into the categories of Group Work, Contribution to Professional Knowledge and Being an Effective Citizen. In the Cognitive Field theme, the students' experiences after museum training are divided into the categories of Field Knowledge, Museum Use Learning and Creativity. In the affective Thinking, Contribution to Professional Knowledge, Permanent Learning, and Role-Playing are the categories of the affective categories. Participants stated that to make use of museum to effect on the cognitive area more effective than affective area.